Les formes « situées » de l’explicitation de l’action comme dévoilement des savoirs issus de la pratique : le cas des interactions en formation professionnelle initiale - Laurent Filliettaz (Recherches en Éducation)
When practitioners meet with researchers in the natural conditions of their ordinary activites, they often provide spontaneous comments in which they reflect on various dimensions of their professional practice. This paper proposes to explore the methodological potentialities and limitations of these verbal productions in order to illuminate the relations between research and practice in the context of vocational education. To do so, the paper refers to a research program currently conducted on teaching and learning within the Swiss dual VET system. Although this program focuses mainly on interactions between apprentices and various sorts of experts in vocational schools and training companies, it provides empirical evidence regarding the ways teachers or trainers interact with researchers during ordinary teaching or working activities. The paper proposes an empirical approach to these sequences of interaction and uses these data in order to illustrate the variety and complexity of vocational knowledge trainers are able to reflect on when making their actions accountable to researchers in such contexts.